Value Added Tax Restitution Process in an Effort to Protect the Rights of Corporate Taxpayers at Massaniga & Rekan Tax Consultant Office - Muhammad Khaedar Sahib; Muhammad Adil; Alfarah Firdamayanti (Universitas Muhammadiyah Makassar, 2023)
Tax restitution is an application for the return of tax overpayments made by taxpayers to the state. This tax overpayment is actually a basic right for taxpayers which otherwise becomes an obligation of the tax authority The purpose of this research is to find out the value-added tax restitution process in an effort to protect the rights of corporate taxpayers at the Massaniga & Rekan Tax Consultant Office. The research object of this Final Project is